Ex vivo all-trans retinoic acid modulates NO production and regulates IL-6 effect during rheumatoid arthritis: a study in Algerian patients. (4th March 2017) - Arroul-Lammali, Amina; Rahal, Fadia; Chetouane, Radia; Djeraba, Zineb; Medjeber, Oussama; Ladjouze-Rezig, Aicha; Touil-Boukoffa, Chafia
Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease. The pathophysiology of RA implicates several mediators such as nitric oxide (NO) and cytokines such as interleukin-6 (IL-6), which is deeply involved in the main characteristics of RA. Furthermore, all- trans retinoic acid (ATRA) is an active vitamin A derivative well-known to have diverse immunomodulatory actions. In our study, we investigated first, the ex vivo immunomodulatory potential of ATRA on NO pathway by peripheral blood mononuclear cells (PBMCs) from Algerian RA patients. Then, we assessed the possible regulatory effect of ATRA on NO production induced by IL-6. PBMCs isolated from active and inactive RA patients and healthy controls were cultured with different concentrations of IL-6 or/with ATRA. NO production was assessed using the Griess method. Inducible nitric oxide synthase expression and NF-κB activity were analyzed by immunofluorescence test. Our results revealed a high NO production during active RA. We noticed that while IL-6 induced a high NO production and iNOS expression, ATRA downregulated both. ATRA also inhibited nuclear NF-κB translocation. Interestingly, it seems that NO production mediated by IL-6 on PBMCs of RA patients is downregulated by ATRA. Taken together, our results highlight the immunomodulatory effect of ATRA on NO pathway in RA patients and its possible role in regulating IL-6-mediated NO production. All these findings suggest its potential therapeutic role during RA.